2011
DOI: 10.1007/978-1-61779-439-1_9
|View full text |Cite
|
Sign up to set email alerts
|

Control of the Interferon Response in RNAi Experiments

Abstract: The RNA interference (RNAi) and interferons have been an uneasy marriage. Ever since the discovery of RNAi in mammals, the interferon response has been a feared problem. While RNAi became an efficient and widespread method for gene silencing in mammals, numerous studies recognized several obstacles, including undesirable activation of the interferon response, which need to be overcome to achieve a specific and robust RNAi effect. The aim of this text is to provide theoretical and practical information for scie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…This inhibition of RPA ubiquitination correlated precisely with decreases in His-ubiquitin levels rather than PRP19 depletion (Figures S4B, S4C). We suspect that this artifact is mediated by the interferon response, which normally detects long double-stranded RNAs but is also known to occur with siRNAs (Nejepinska et al, 2012). Interferon can inhibit expression from exogenous CMV promoters (Harms and Splitter, 1995).…”
Section: Resultsmentioning
confidence: 99%
“…This inhibition of RPA ubiquitination correlated precisely with decreases in His-ubiquitin levels rather than PRP19 depletion (Figures S4B, S4C). We suspect that this artifact is mediated by the interferon response, which normally detects long double-stranded RNAs but is also known to occur with siRNAs (Nejepinska et al, 2012). Interferon can inhibit expression from exogenous CMV promoters (Harms and Splitter, 1995).…”
Section: Resultsmentioning
confidence: 99%
“…As the activation of the immune response has been described as a potential off-target effect induced after siRNA transfection, we questioned whether the four sequences were able to activate the innate immune signalling through Toll-like receptors [TLRs]. 28 We used the NFkB reporter cell line THP1-XBlue-MD2-CD14 [further referred to as THP1-XBlue cells], derived from the human monocytic THP1 cells. THP1-XBlue cells were exposed to siRNAs at a final concentration of 10 nM.…”
Section: Resultsmentioning
confidence: 99%
“…a,b). It was reported that the IFN response is one of the most common non‐specific effects of RNAi experiments . To eliminate the possible confounding effects of a shRNA/shNC inducible IFN response, simvastatin, an inhibitor of HMGCR, was used.…”
Section: Discussionmentioning
confidence: 99%